2018
DOI: 10.1177/1042258718807696
|View full text |Cite
|
Sign up to set email alerts
|

The Direct and Indirect Impact of Gender Diversity in New Venture Teams on Innovation Performance

Abstract: Women's interest and participation in entrepreneurship is growing. The limited and inconclusive findings on such growth have made it difficult to characterize its influence on new venture innovation performance. In addressing this issue, our study found a positive relationship between the gender diversity scores of new venture teams—reflecting the increased presence of women—and the innovation performance of new ventures. It also found the positive influence of gender diversity on (a) the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 84 publications
3
78
1
2
Order By: Relevance
“…Kushnirovich and Heilbrunn [50], who use a survey from Israel, find that culture, rather than gender, has a significant impact on innovation. However, it is contrary to results of Østergaard et al [25], Horbach and Jacob [45], Nielsen, Bloch, and Schiebinger [46], and Dai, Byun, and Ding [47]. These studies find that gender diversity improves innovation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Kushnirovich and Heilbrunn [50], who use a survey from Israel, find that culture, rather than gender, has a significant impact on innovation. However, it is contrary to results of Østergaard et al [25], Horbach and Jacob [45], Nielsen, Bloch, and Schiebinger [46], and Dai, Byun, and Ding [47]. These studies find that gender diversity improves innovation.…”
Section: Discussionmentioning
confidence: 62%
“…Nielsen, Bloch, and Schiebinger [46] find that gender diversity of employees can positively influence scientific discovery and innovation by three approaches to gender diversity: (1) diversity in research teams, (2) diversity in research methods, and (3) diversity in research questions. Furthermore, in the context of new ventures, there is a positive relationship between the gender diversity of new venture firms and their innovation performance [47].…”
Section: The Effect Of Gender On Innovationmentioning
confidence: 99%
“…This result differs from other studies that show that gender diversity at the firm level may be beneficial for innovation (Diaz-Garcia et al, 2014;Garcia Martinez et al, 2016;Horbach and Jacob, 2018;Østergaard et al, 2011;Ruiz-Jiménez et al, 2016). Very recently, Dai et al (2019) also found a positive relationship between the gender diversity of new venture teams and their innovation performance. Beyond innovation outcomes, gender diversity also fosters strategic change (Triana et al, 2019) and, ultimately, organizational performance (Salloum et al, 2019;Gonzalez and Denisi, 2009).…”
Section: Theoretical Contributionsmentioning
confidence: 91%
“…Therefore, gender equality in the workplace should not be overlooked. The previous study shows that gender diversity has a strong positive relationship to innovation capability performance [3] [11]. It could also increase market valuation and revenue [12].…”
Section: Gender Diversitymentioning
confidence: 99%
“…It is important to involve a woman in the organization. The impact of gender diversity on innovation performance has been proven [3]. Companies that are gender-diverse and utilise female talent effectively are 45% more likely to report improved market share [4].…”
Section: Introductionmentioning
confidence: 99%